ANALISIS PROSEDUR PENGELOLAAN DANA KAS KECIL PADA PT AXIA MULTI SARANA - Fahira Mutia Sodi, (2023)
PT Axia Multi Sarana is a company engaged in the distribution of machinery such as pumping machines, chemical machines and others. Petty cash is very necessary in the operational activities of a company. With the establishment of a petty cash fund it will facilitate the performance of office administration, secretaries or accountants who will carry out transactions in relatively small amounts. This research was conducted with the aim of understanding the procedures for managing petty cash funds at PT Axia Multi Sarana. In this writing, data and information obtained through observation, interviews and documentation are then collected and processed through descriptive methods. Where data and information management is carried out by explaining or telling or describing the procedures for managing petty cash funds at PT Axia Multi Sarana in sentence form so as to facilitate data interpretation. The results of the study show that PT Axia Multi Sarana in managing the petty cash fund uses a fixed fund system.